Introduction to Bioinformatics - Arthur M. Lesk (Oxford University Press, 2014)
Fully revised and updated, the fourth edition of Introduction to Bioinformatics shows how bioinformatics can be used as a powerful set of tools for retrieving and analyzing this biological data, and how bioinformatics can be applied to a wide range of disciplines such as molecular biology, medicine, biotechnology, forensic science, and anthropology. This new edition contains two new chapters, with significantly increased coverage of metabolic pathways, and gene expression and regulation. Written for students without a detailed prior knowledge of programming, this book is the perfect introduction to the field of bioinformatics, providing friendly guidance and advice on how to use various methods and techniques. Additionally, frequent examples, self-test questions, problems, and exercises are incorporated throughout the text to encourage self-directed learning.